Gambaran Kepatuhan Pasien Dalam Menjalani Perawatan Saluran Akar Di RSKGM FKG Universitas Indonesia - Nurul Annisa; Astri Annur Qalbi; St Nur Eni; Febi Magfirah; Tri Hesti Hastuti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Oral and dental health is an important indicator of overall health, well-being, and quality of life. Root canal treatment is one of the conventional endodontic procedures aimed at cleaning vital or necrotic pulp tissue within the root canal. However, root canal treatment requires multiple visits. The large number of visits needed for this treatment often leads to patient noncompliance, which may result in incomplete treatment. This study is a descriptive study conducted on patients at the Conservation Clinic of RSKGM FKG Universitas Indonesia during May–June 2025. The population consisted of all patients seeking treatment at RSKGM FKG Universitas Indonesia. Samples were taken using purposive sampling with criteria of patients currently undergoing root canal treatment (RCT), aged over 18 years, and willing to participate as respondents. The results showed that most patients undergoing root canal treatment were in the noncompliant category, with 60 people (92.3%), and no patients were found to be compliant in undergoing RCT. Female patients in the noncompliant category accounted for 33 people (50.8%). Most respondents aged 18–40 years were also in the noncompliant category, totaling 36 people (55.4%). The highest number of noncompliant respondents were those with a bachelor’s degree (S1), totaling 30 people (46.2%). In conclusion, patient compliance in undergoing root canal treatment at RSKGM FKG Universitas Indonesia falls into the noncompliant category.